Rachunek kosztów cyklu życia produktu bankowego - Paradecki, Robert (Product Life Cycle Costing in a Bank, 2006)
The cost of money is very important for a bank manager. Money, as every product, has its own life cycle. When a bank manager knows the duration of this cycle, then the balance of the monetary incomes and expenditures of an enterprise is bigger and bank activity is better and more effective. Activity based costing is one of many methods of cost management, but it is better than the traditional methods.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1139, s. 310-321